Trade associations, bureaucracies, and productive credit in Colombia, 1958-1974 - Fernando Chisnes-Espitia (Íconos)
The paper analyzes the relation between economic elites and the Colombian State around the development credit policy. It explores specifically the term between 1958 and 1974 and studies State capture expression in the developmental period, it deepens in the way in which elites define or influence in the credit policy direction. The case of study allows to reveal the ways in which the State acquire more autonomy regard elites. The argument is that State autonomy depends on two main factors: the level o dependency of high bureaucracies regarding economic elites on one side, and the relational process of the Sate with the social groups involved in the specific policy. Using a Social Network analysis related to the high bureaucracies of the Central Bank of Colombia and the study of interactions between produces associations (as organized agent of the economic elites) with the State it studies the mechanism in which the relation State and economic elites impact the specific policy of development credit.